Incidence and Risk of Hypertension in Cancer Patients Treated With Atezolizumab and Bevacizumab: A Systematic Review and Meta-Analysis - Jiang, Linhan; Tan, Xiaoxia; Li, Jun; Li, Yaling (Frontiers in Oncology, 2021)
Purpose: To better understand the total risk of hypertension with atezolizumab plus bevacizumab in cancer patients, this study contributes to inform an earlier clinical assessment and reduce the incidence of hypertension-related cardiovascular complications. Methods: Databases, including PubMed, Embase, and Web of Science were searched to identify relevant studies from inception to March 6, 2021. Studies of patients with cancer assigned atezolizumab plus bevacizumab with data on hypertension available were eligible for inclusion. Statistical analyses were conducted to calculate the hypertension incidence and relative risk (RR) with a random-effects or fixed-effects model, hinging on the heterogeneity status. Results: Ten studies included a total of 2106 patients with renal cell carcinoma (RCC), hepatocellular carcinoma (HCC), ovarian cancer, anal cancer, neuroendocrine tumors (NETs) and cervical cancer were selected for this meta-analysis. For patients assigned atezolizumab-bevacizumab, the all-grade and high-grade (ie, grade 3 or 4) hypertension incidence were 31.1% (95% CI: 25.5-37.3) and 14.1% (95% CI: 10.9-18.1), respectively. No significant difference was observed in all-grade hypertension incidence between RCC and a non-RCC patients (32.9% [95% CI: 25.3-42.6] v.s. 29.2% [95% CI: 19.7-39.6)]) who were assigned atezolizumab-bevacizumab, but the high-grade hypertension incidence in RCC patients (9.4% [95% CI: 4.1-21.3]) is lower than who with non-RCC (15.6% [95% CI: 12.8-19.1]). Cancer Patients who received the treatment of atezolizumab plus bevacizumab was associated with a significantly increased risk of all-grade hypertension with a RR of 7.22 (95% CI: 3.3-15.7; p = 0.6) compared with who received atezolizumab. Conclusions: Cancer Patients who received atezolizumab plus bevacizumab have a significantly increased risk of hypertension. Early detection, adequate monitoring and aggressive treatment are highly recommended to prevent hypertension and other cardiovascular complications of drug combination.